高エネルギー降下粒子がNa層に与える影響に関する化学モデル計 - 滝沢, 響吾; 津田, 卓雄; Kyogo, Takizawa; Takuo, T. Tsuda (2017)
第8回極域科学シンポジウム/横断セッション：[IW] 全大気圏 －南極地域観測第Ⅷ期・第Ⅸ期重点研究観測の活動を含めて－ 12月6日（水）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Interdisciplinary sessions: [IW] Whole atmosphere - including activities of JARE phase VIII and IX prioritized projects - Wed. 6 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object